Colonic Leucine-Rich Repeat Kinase 2 Expression Is Increased and Associated With Disease Severity in Patients With Parkinson’s Disease - Liao, Peng-Hsiang; Chiang, Han-Lin; Shun, Chia-Tung; Hang, Jen-Fan; Chiu, Han-Mo; Wu, Ming-Shiang; Lin, Chin-Hsien (Frontiers in Aging Neuroscience, 2022)
Background Mutations in leucine-rich repeat kinase 2 (LRRK2) comprise a common genetic risk factor for Parkinson’s disease (PD) and inflammatory bowel disease (IBD). We investigated the expression of LRRK2 in colonic biopsies obtained from a cohort of PD patients and healthy controls. Methods A cohort of 51 PD patients and 40 age- and gender-matched controls who have colonic biopsied samples were recruited. Among these participants, 26 individuals (12 PD patients and 14 controls) had a series of colon biopsies. For the patients with PD, the first biopsies were taken before the PD diagnosis. The colonic expression of LRRK2 was assayed by immunohistochemical staining. Results The fraction of LRRK2-positive cells among the total cell count in biopsied colonic tissues was significantly higher in PD patients than controls (0.81% ± 0.53% vs. 0.45% ± 0.39%; P = 0.02). Colonic LRRK2 immunoreactivity was higher in those with LRRK2 genetic variants compared to those with wild type LRRK2 (2.44% ± 1.15% vs. 0.21 ± 0.13%, P < 0.01). Age had no effect on LRRK2 expression (P = 0.96). LRRK2 expression correlated with disease severity in regards to motor symptoms measured by the UPDRS part III scores (r = 6335, P < 0.001) and cognitive dysfunction measured by the mini-mental status examination scores (r = -0.5774, P < 0.001). PD patients in the prodromal phase had a steeper increase in colonic LRRK2 expression compared to controls during the serial colon biopsy assessment (P < 0.01). Conclusion Colonic LRRK2 expression was increased in PD patients compared to controls, and the expression level correlated with disease severity.